Event-Related Potentials and executive control deficits in major depression: evidence from the Attention Network Test - Kustubayeva, Almira; Zholdassova, Manzura; Kamzanova, Altyngul; Madaliyeva, Zabira; Suleimenova, Aigul; Nessipbayev, Sultangali; Borbassova, Gulnur; Arman, Diana; Nelson, Erik; Matthews, Gerald (Frontiers in Systems Neuroscience, 2026)
ObjectiveBehavioral and neurological studies suggest that major depressive disorder (MDD) is associated with pervasive deficits in executive control of attention. Research using Event-Related Potentials (ERPs) to investigate attentional impairments in depression has provided mixed results. The current study aimed to clarify abnormalities in ERPs associated with depression through use of the Attention Network Test (ANT) which assesses efficiency of three fundamental brain networks: executive control, alerting, and orienting.MethodsParticipants were 93 volunteers. We compared ERP amplitudes in healthy, subsyndromal depression, and MDD groups (31 participants per group) during performance of an extended-duration version of the ANT.ResultsBoth N100 and P300 ERP amplitudes were generally lower in the MDD group across central-parietal and posterior sites, with medium-to-large effect sizes. There were also significant effects of depression on the ANT indices for executive control and alerting. Further analyses showed that some abnormalities in ERPs were seen in the subsyndromal group and that depression effects were stable across time, despite vigilance decrement.ConclusionNeurocognitive deficits in depression may relate to depletion of a general attentional resource.